Optical fiber ribbon and optical fiber cable
Patent Information
- Application Number
- JP2022505801
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-09
- Filing Date
- 2021-01-18
- Publication Date
- 2025-03-27
- Estimated Expiration
- 2041-01-18
AI Technical Summary
【0009】 [本開示の効果] 本開示によれば、細径の光ファイバを用いた場合に、耐剥離性と単心分離性との両立が可能であり、光ケーブルの伝送損失の増加を抑制することができる光ファイバリボンを提供することができる。
Smart Images

Figure 0007652184000003 
Figure 0007652184000004 
Figure 0007652184000005
Abstract
Description
[Technical field]
[0001] The present disclosure relates to optical fiber ribbons and optical fiber cables. This application claims priority to Japanese Application No. 2020-039645, filed on March 9, 2020, and incorporates by reference all of the contents of said Japanese application. [Background technology]
[0002] Generally, an optical fiber core has a thin colored layer called an ink layer as its outermost layer in order to identify an optical fiber wire composed of a glass fiber and a resin coating layer covering the glass fiber (see, for example, Patent Document 1).
[0003] There is known an optical fiber ribbon in which a plurality of optical fibers are arranged and integrated with a collective coating layer. For example, Patent Document 2 discloses that optical fibers having an outer diameter of 220 μm or less are connected with a resin in order to achieve high density thinning of an optical fiber cable containing optical fiber ribbons. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 6-242355 [Patent Document 2] JP 2013-88617 A Summary of the Invention
[0005] An optical fiber ribbon according to one embodiment of the present disclosure has a plurality of optical fibers arranged in parallel, and a connecting resin layer containing a ribbon resin that coats and connects the plurality of optical fibers, each of the plurality of optical fibers having an outer diameter of 220 μm or less, and each of the plurality of optical fibers includes a glass fiber including a core and a cladding, a primary resin layer that contacts the glass fiber and coats the glass fiber, and a colored secondary resin layer that coats the primary resin layer, and the colored secondary resin layer contains 2,4,6-trimethylbenzoyldiphenylphosphine as a photopolymerization initiator. Oxide The colored secondary resin layer has a phosphorus content of 0.03 mass % or more and 0.30 mass % or less, and a phosphorus-tin complex on the surface of the colored secondary resin layer is 300 ppm or more and 7000 ppm or less. [Brief description of the drawings]
[0006] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of an optical fiber. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing an optical fiber ribbon according to an embodiment. [Diagram 3] FIG. 3 is a schematic cross-sectional view showing an optical fiber ribbon according to an embodiment. [Figure 4] FIG. 4 is a plan view showing the appearance of an intermittent optical fiber ribbon according to an embodiment. [Diagram 5] FIG. 5 is a schematic cross-sectional view showing an optical fiber ribbon according to an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] [Problem that this disclosure aims to solve] When winding an optical fiber ribbon onto a bobbin or forming it into an optical cable, a small-diameter optical fiber is more susceptible to lateral pressure due to bending than an optical fiber with an outer diameter of 250 μm, and therefore has poor resistance to lateral pressure and is more likely to increase transmission loss. In addition, in the case of an optical fiber ribbon using a small-diameter optical fiber, the contact area between the optical fiber and the ribbon resin coating the optical fiber is small, so if the ribbon resin has low adhesion to the optical fiber, the ribbon resin is likely to peel off. On the other hand, if the ribbon resin has too high adhesion to the optical fiber, it becomes difficult to separate the optical fibers into single fibers when fixing the end of the optical fiber ribbon.
[0008] The present disclosure aims to provide an optical fiber ribbon that can achieve both peel resistance and single-core separation resistance when using a small-diameter optical fiber, and can suppress an increase in transmission loss in an optical cable.
[0009] [Effects of this disclosure] According to the present disclosure, when a small diameter optical fiber is used, it is possible to provide an optical fiber ribbon that can achieve both peel resistance and single-core separation properties and suppress an increase in transmission loss in an optical cable.
[0010] [Description of the embodiments of the present disclosure] First, the contents of the embodiment of the present disclosure will be listed and described. An optical fiber ribbon according to one aspect of the present disclosure is an optical fiber ribbon having a plurality of optical fibers arranged in parallel and a connecting resin layer containing a ribbon resin that covers and connects the plurality of optical fibers, the outer diameter of each of the plurality of optical fibers is 220 μm or less, each of the plurality of optical fibers includes a glass fiber including a core and a clad, a primary resin layer that contacts the glass fiber and covers the glass fiber, and a colored secondary resin layer that covers the primary resin layer, and the colored secondary resin layer contains 2,4,6-trimethylbenzoyldiphenylphosphine as a photopolymerization initiator. OxideThe colored secondary resin layer has a phosphorus content of 0.03 mass% or more and 0.30 mass% or less, and the amount of phosphorus-tin complex on the surface of the colored secondary resin layer is 300 ppm or more and 7000 ppm or less.
[0011] The optical fiber ribbon of this embodiment is capable of achieving both peel resistance and individual core separation properties, and can be bent sharply when packed densely within a cable, and can suppress an increase in transmission loss when wound around a bobbin or cabled.
[0012] In order to obtain an optical fiber ribbon having excellent bulk fusion properties, the amount of the phosphorus-tin complex is preferably 500 ppm or more and 6000 ppm or less. m It is preferable that the thickness is 280 μm or more.
[0013] Since the adhesion between the colored secondary resin layer and the ribbon resin can be easily adjusted, the resin composition may further contain a polyfunctional monomer having a bisphenol skeleton, and may further contain a silicone-based lubricant.
[0014] The resin composition may further contain 1-hydroxycyclohexyl phenyl ketone as a photopolymerization initiator, since this provides better single-core separation properties for the optical fiber.
[0015] The Young's modulus of the colored secondary resin layer is preferably 1200 MPa or more at 23° C., since this can further suppress an increase in the transmission loss of the optical cable.
[0016] Since the optical fiber ribbon is easily deformed when being housed in a cable, the optical fiber ribbon according to this embodiment may have connected portions and non-connected portions intermittently in the longitudinal and width directions.
[0017] Since the optical fiber ribbon is easily deformed when being housed in a cable, the connecting resin layer may have a recess in a portion that connects adjacent optical fibers among the plurality of optical fibers.
[0018] An optical fiber cable according to an aspect of the present disclosure includes the optical fiber ribbon mounted within the cable. The optical fiber cable including the optical fiber ribbon according to this embodiment can achieve both high lateral pressure characteristics and low transmission loss.
[0019] [Details of the embodiment of the present disclosure] Specific examples of optical fiber ribbons and optical fiber cables according to embodiments of the present disclosure will be described with reference to the drawings as necessary. The present disclosure is not limited to these examples, but is indicated by the claims, and is intended to include all modifications within the meaning and scope equivalent to the claims. In the following description, the same elements in the description of the drawings will be given the same reference numerals, and duplicated descriptions will be omitted. In this embodiment, (meth)acrylate means acrylate or the corresponding methacrylate, and the same applies to other similar expressions such as (meth)acryloyl.
[0020] <Optical fiber ribbon> In the optical fiber ribbon according to the present embodiment, a plurality of optical fibers arranged in parallel are coated with a ribbon resin, which connects the plurality of optical fibers to form a connecting resin layer.
[0021] 1 is a schematic cross-sectional view showing an example of an optical fiber 10. The optical fiber 10 includes a glass fiber 13 including a core 11 and a cladding 12, and a coating resin layer 16 including a primary resin layer 14 and a colored secondary resin layer 15 provided on the outer periphery of the glass fiber 13.
[0022] The cladding 12 surrounds the core 11. The core 11 and the cladding 12 mainly contain glass such as silica glass, and for example, the core 11 can be made of silica glass doped with germanium or pure silica glass, and the cladding 12 can be made of pure silica glass or silica glass doped with fluorine.
[0023] 1, the outer diameter of the optical fiber 10 is 220 μm or less, and may be 140 μm or more and 220 μm or less, or 170 μm or more and 220 μm or less. The outer diameter (D2) of the glass fiber 13 may be about 100 μm to 125 μm, and the diameter (D1) of the core 11 constituting the glass fiber 13 may be about 7 μm to 15 μm. The thickness of each of the primary resin layer 14 and the colored secondary resin layer 15 may be about 5 μm to 50 μm.
[0024] The colored secondary resin layer 15 can be formed, for example, by curing an ultraviolet-curable resin composition containing a photopolymerizable compound, a photopolymerization initiator, and a pigment. The above-mentioned resin composition contains 2,4,6-trimethylbenzoyldiphenylphosphine oxide (Omnirad TPO, manufactured by IGM Resins, hereinafter abbreviated as "TPO") as a photopolymerization initiator as an essential component, and the colored secondary resin layer 15 contains 2,4,6-trimethylbenzoyldiphenylphosphine oxide (Omnirad TPO, manufactured by IGM Resins, hereinafter abbreviated as "TPO") as a photopolymerization initiator. Oxide and a cured product of the resin composition containing the above.
[0025] TPO, a phosphorus-based photopolymerization initiator, is effective in enhancing the curing property of the coating resin layer. Meanwhile, it is known that phosphorus (P) forms a complex (P-Sn complex) with tin (Sn). Tin catalysts are sometimes used as catalysts for synthesizing urethane, and in that case, tin remains in the urethane (meth)acrylate. When TPO is used as a photopolymerization initiator and urethane (meth)acrylate is used as a photopolymerizable compound, the phosphorus derived from TPO and the tin mixed in the urethane (meth)acrylate form a P-Sn complex in the secondary resin layer. If the P-Sn complex is unevenly distributed on the surface of the secondary resin layer, the adhesion at the interface between the secondary resin layer and the ribbon resin during the preparation of the optical fiber ribbon decreases, and peeling is likely to occur during the preparation of the optical fiber ribbon.
[0026] In contrast, in the optical fiber of this embodiment, the phosphorus content in the colored secondary resin layer 15 is 0.03 mass% or more and 0.30 mass% or less, and the amount of P-Sn complex on the surface of the colored secondary resin layer 15 is 300 ppm or more and 7000 ppm or less, thereby making it possible to achieve both the curability and adhesion of the colored secondary resin layer.
[0027] The phosphorus content may be 0.05% by mass or more and 0.28% by mass or less, or 0.07% by mass or more and 0.27% by mass or less. The content of phosphorus that forms a complex with tin can be adjusted by the amount of TPO blended in the resin composition. The phosphorus content can be measured by ICP emission spectrometry. Specifically, 20 mL of sulfuric acid and 6 mL of nitric acid are added to 1 g of a resin composition for forming a colored secondary resin layer, and the mixture is heated for 10 minutes, and then 4 mL of perchloric acid is added and the mixture is heated until no insoluble matter remains. The mixture is then diluted with water to a constant volume of 100 mL, and measured by ICP emission spectrometry.
[0028] In order to obtain a more excellent single-core separation property of the optical fiber, the amount of the P-Sn complex is preferably 400 ppm or more and 6500 ppm or less, more preferably 500 ppm or more and 6000 ppm or less, and even more preferably 3300 ppm or more and 6000 ppm or less. The amount of the P-Sn complex can be adjusted by the blending amount of TPO and urethane (meth)acrylate in the resin composition. The amount of the P-Sn complex can be measured by analyzing the surface of the coating resin layer using TOF-SIMS. In this specification, the amount of the P-Sn complex (ppm) is a mass ratio.
[0029] The resin composition may further contain other photopolymerization initiators. The other photopolymerization initiators may be appropriately selected from known radical photopolymerization initiators. Examples of the other photopolymerization initiators include 1-hydroxycyclohexyl phenyl ketone (Omnirad 184, manufactured by IGM Resins), 2,2-dimethoxy-2-phenylacetophenone, 1-(4-isopropylphenyl)-2-hydroxy-2-methylpropan-1-one, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholino-propan-1-one (Omnirad 907, manufactured by IGM Resins), and bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (Omnirad 819, manufactured by IGM Resins).
[0030] As the other photopolymerization initiator, a photopolymerization initiator that does not form a complex with tin is preferable, and Omnirad 184 is more preferable. The above resin composition can further improve the single-core separation property of the optical fiber by using 2,4,6-trimethylbenzoyldiphenylphosphine oxide and 1-hydroxycyclohexyl phenyl ketone in combination as the photopolymerization initiator.
[0031] The colored secondary resin layer 15 contains a pigment to form a colored layer that serves as an ink layer for identifying the optical fiber. Examples of the pigment include colored pigments such as carbon black, titanium oxide, and zinc oxide, mixed crystals of γ-Fe2O3 and γ-Fe3O4, CrO2, cobalt ferrite, cobalt-coated iron oxide, barium ferrite, magnetic powders such as Fe-Co and Fe-Co-Ni, inorganic pigments such as MIO, zinc chromate, strontium chromate, aluminum tripolyphosphate, zinc, alumina, glass, and mica, and organic pigments such as azo pigments, phthalocyanine pigments, and dye lake pigments. The pigments may be subjected to various surface modification treatments, composite pigmentation, and the like.
[0032] The photopolymerizable compound may include oligomers and monomers. The oligomers include, for example, urethane (meth)acrylates and epoxy (meth)acrylates.
[0033] The urethane (meth)acrylate may be a compound obtained by reacting a polyol compound, a polyisocyanate compound, and a hydroxyl group-containing (meth)acrylate compound.
[0034] Examples of the polyol compound include polytetramethylene glycol, polypropylene glycol, and bisphenol A-ethylene oxide addition diol. From the viewpoint of adjusting the Young's modulus, the number average molecular weight of the polyol compound may be 300 or more and 8000 or less. Examples of the polyisocyanate compound include 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, isophorone diisocyanate, and dicyclohexylmethane 4,4'-diisocyanate. Examples of the hydroxyl group-containing (meth)acrylate compound include 2-hydroxyethyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 1,6-hexanediol mono(meth)acrylate, pentaerythritol tri(meth)acrylate, 2-hydroxypropyl (meth)acrylate, and tripropylene glycol (meth)acrylate.
[0035] As a catalyst for synthesizing urethane (meth)acrylate, an organometallic catalyst may be used, and from the viewpoint of manufacturability, an organotin compound may be used. Examples of organotin compounds include dibutyltin dilaurate, dibutyltin diacetate, dibutyltin maleate, dibutyltin bis(2-ethylhexyl mercaptoacetate), dibutyltin bis(isooctyl mercaptoacetate), and dibutyltin oxide. From the viewpoint of easy availability or catalytic performance, it is preferable to use dibutyltin dilaurate or dibutyltin diacetate as a catalyst. From the viewpoint of productivity, it is desirable to use a large amount of catalyst, but it is desirable to set it to an appropriate range so that it precipitates on the resin layer surface and easily reduces the adhesion between the ribbon resin and the colored secondary resin layer.
[0036] A lower alcohol having 5 or less carbon atoms may be used during synthesis of the urethane (meth)acrylate. Examples of the lower alcohol include methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, 2-methyl-2-propanol, 1-pentanol, 2-pentanol, 3-pentanol, 2-methyl-1-butanol, 3-methyl-1-butanol, 2-methyl-2-butanol, 3-methyl-2-butanol, and 2,2-dimethyl-1-propanol.
[0037] Epoxy (meth)acrylate is a compound obtained by reacting an epoxy compound having two or more glycidyl groups with a compound having a (meth)acryloyl group.
[0038] The monomer may be a monofunctional monomer having one polymerizable group or a polyfunctional monomer having two or more polymerizable groups. Two or more kinds of monomers may be mixed and used.
[0039] Examples of the monofunctional monomer include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, s-butyl (meth)acrylate, tert-butyl (meth)acrylate, isobutyl (meth)acrylate, n-pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, isoamyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, 2 ... octyl (meth)acrylate, isooctyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, 2-phenoxyethyl (meth)acrylate, 3-phenoxybenzyl acrylate, phenoxydiethylene glycol acrylate, phenoxypolyethylene glycol acrylate, 4-tert-butylcyclohexanol acrylate, tetrahydrofurfuryl (meth)acrylate, benzyl (meth)acrylate, dicyclopentenyl (meth)acrylate, (Meth)acrylate monomers such as dicyclopentenyloxyethyl (meth)acrylate, dicyclopentanyl (meth)acrylate, nonylphenol polyethylene glycol (meth)acrylate, nonylphenol EO modified acrylate, nonylphenoxy polyethylene glycol (meth)acrylate, and isobornyl (meth)acrylate; (meth)acrylic acid, (meth)acrylic acid dimer, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, ω-carboxy -Carboxyl group-containing monomers such as polycaprolactone (meth)acrylate; heterocycle-containing (meth)acrylates such as N-acryloylmorpholine, N-vinylpyrrolidone, N-vinylcaprolactam, N-acryloylpiperidine, N-methacryloylpiperidine, N-acryloylpyrrolidine, 3-(3-pyridyl)propyl (meth)acrylate, and cyclic trimethylolpropane formal acrylate; maleimide-based monomers such as maleimide, N-cyclohexylmaleimide, and N-phenylmaleimide;N-substituted amide monomers such as (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N-hexyl(meth)acrylamide, N-methyl(meth)acrylamide, N-ethyl(meth)acrylamide, N-butyl(meth)acrylamide, N-methylol(meth)acrylamide, and N-methylolpropane(meth)acrylamide; aminoalkyl(meth)acrylate monomers such as aminoethyl(meth)acrylate, aminopropyl(meth)acrylate, N,N-dimethylaminoethyl(meth)acrylate, and tert-butylaminoethyl(meth)acrylate; and succinimide monomers such as N-(meth)acryloyloxymethylenesuccinimide, N-(meth)acryloyl-6-oxyhexamethylenesuccinimide, and N-(meth)acryloyl-8-oxyoctamethylenesuccinimide.
[0040] Examples of polyfunctional monomers include ethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, di(meth)acrylate of an alkylene oxide adduct of a bisphenol compound, tetraethylene glycol di(meth)acrylate, hydroxypivalic acid neopentyl glycol di(meth)acrylate, 1,4 -Butanediol di(meth)acrylate, 1,6-Hexanediol di(meth)acrylate, 1,9-Nonanediol di(meth)acrylate, 1,12-Dodecanediol di(meth)acrylate, 1,14-Tetradecanediol di(meth)acrylate, 1,16-Hexadecanediol di(meth)acrylate, 1,20-Eicosanediol di(meth)acrylate, Isopentyldiol di(meth)acrylate, 3-Ethyl-1,8-Octanediol di(meth)acrylate, Bisphenol EO adduct di(meth)acrylate of nol compound, trimethylolpropane tri(meth)acrylate, trimethyloloctane tri(meth)acrylate, trimethylolpropane polyethoxy tri(meth)acrylate, trimethylolpropane polypropoxy tri(meth)acrylate, trimethylolpropane polyethoxy polypropoxy tri(meth)acrylate, tris[(meth)acryloyloxyethyl]isocyanurate, pentaerythritol tri(meth)acrylate, pentaerythritol Examples of the polyether acrylates include erythritol polyethoxy tetra(meth)acrylate, pentaerythritol polypropoxy tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and caprolactone-modified tris[(meth)acryloyloxyethyl]isocyanurate.
[0041] Examples of the bisphenol compound include bisphenol A, bisphenol AP, bisphenol B, bisphenol BP, bisphenol C, and bisphenol E. As the polyfunctional monomer, a polyfunctional monomer having a bisphenol skeleton can be used, and among them, it is preferable to use a polyfunctional monomer having a bisphenol A skeleton. By adjusting the amount of the polyfunctional monomer having a bisphenol A skeleton, it becomes easy to adjust the surface deposition amount of the P-Sn complex. As the polyfunctional monomer having a bisphenol skeleton A, an epoxy acrylate having a bisphenol A skeleton may be used.
[0042] In order to further enhance adhesion with the ribbon resin, the content of the polyfunctional monomer having a bisphenol skeleton in the colored secondary resin layer may be 25% by mass or more and 80% by mass or less, 30% by mass or more and 75% by mass or less, or 40% by mass or more and 70% by mass or less, based on the total amount of the resin composition for forming the colored secondary resin layer.
[0043] The resin composition may further contain a silane coupling agent, inorganic oxide particles, a lubricant, a photoacid generator, a leveling agent, an antifoaming agent, an antioxidant, a sensitizer, and the like.
[0044] Silane coupling agents are not particularly limited as long as they do not interfere with the curing of the resin composition. Examples of silane coupling agents include tetramethyl silicate, tetraethyl silicate, mercaptopropyl trimethoxysilane, vinyl trichlorosilane, vinyl triethoxysilane, vinyl tris(β-methoxy-ethoxy)silane, β-(3,4-epoxycyclohexyl)-ethyl trimethoxysilane, dimethoxydimethylsilane, diethoxydimethylsilane, 3-acryloxypropyl trimethoxysilane, 3-glycidoxypropyl trimethoxysilane, 3-glycidoxypropyl methyl diethoxysilane, 3-methacryloxypropyl trimethoxysilane, N-(β-aminoethyl)-γ 3-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethyldimethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, 3-chloropropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, bis-[3-(triethoxysilyl)propyl]tetrasulfide, bis-[3-(triethoxysilyl)propyl]disulfide, γ-trimethoxysilylpropyldimethylthiocarbamyltetrasulfide, and γ-trimethoxysilylpropylbenzothiazyltetrasulfide.
[0045] The inorganic oxide particles are not particularly limited. From the viewpoint of excellent dispersibility in the resin composition and easy adjustment of the Young's modulus, the inorganic oxide particles are preferably particles containing at least one selected from the group consisting of silicon dioxide (silica), zirconium dioxide (zirconia), aluminum oxide (alumina), magnesium oxide (magnesia), titanium oxide (titania), tin oxide, and zinc oxide. From the viewpoints of low cost, ease of surface treatment, ultraviolet transmittance, and ease of imparting appropriate hardness to the cured product, it is more preferable to use silica particles as the inorganic oxide particles.
[0046] The inorganic oxide particles are preferably hydrophobic. Specifically, the surfaces of the inorganic oxide particles are preferably hydrophobically treated with a silane compound. Here, the hydrophobic treatment refers to the introduction of a hydrophobic group to the surface of the inorganic oxide particles. The inorganic oxide particles having the hydrophobic group introduced thereto have excellent dispersibility in the resin composition. The hydrophobic group may be an ultraviolet-curable reactive group such as a (meth)acryloyl group or a vinyl group, or a non-reactive group such as a hydrocarbon group (e.g., an alkyl group) or an aryl group (e.g., a phenyl group). When the inorganic oxide particles have a reactive group, it is easy to form a resin layer having a high Young's modulus.
[0047] Examples of silane compounds having a reactive group include silane compounds such as 3-methacryloxypropyltrimethoxysilane, 3-acryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-acryloxypropyltriethoxysilane, 8-methacryloxyoctyltrimethoxysilane, 8-acryloxyoctyltrimethoxysilane, 7-octenyltrimethoxysilane, vinyltrimethoxysilane, and vinyltriethoxysilane.
[0048] Examples of silane compounds having an alkyl group include methyltrimethoxysilane, dimethyldimethoxysilane, ethyltrimethoxysilane, propyltrimethoxysilane, butyltrimethoxysilane, pentyltrimethoxysilane, hexyltrimethoxysilane, octyltrimethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, ethyltriethoxysilane, propyltriethoxysilane, butyltriethoxysilane, pentyltriethoxysilane, hexyltriethoxysilane, and octyltriethoxysilane.
[0049] The inorganic oxide particles may be dispersed in a dispersion medium when added to the resin composition. By using the inorganic oxide particles dispersed in a dispersion medium, the inorganic oxide particles can be uniformly dispersed in the resin composition, and the storage stability of the resin composition can be improved. The dispersion medium is not particularly limited as long as it does not inhibit the curing of the resin composition. The dispersion medium may be reactive or non-reactive.
[0050] As the reactive dispersion medium, monomers such as (meth)acryloyl compounds and epoxy compounds may be used. As the (meth)acryloyl compounds, for example, 1,6-hexanediol di(meth)acrylate, EO modified bisphenol A di(meth)acrylate, polyethylene glycol di(meth)acrylate, PO modified bisphenol A di(meth)acrylate, polypropylene glycol di(meth)acrylate, polytetramethylene glycol di(meth)acrylate, 2-hydroxy-3-phenoxypropyl acrylate, (meth)acrylic acid adduct of propylene glycol diglycidyl ether, (meth)acrylic acid adduct of tripropylene glycol diglycidyl ether, and (meth)acrylic acid adduct of glycerin diglycidyl ether may be used. As the dispersion medium, (meth)acryloyl compounds exemplified in the above-mentioned monomers may be used.
[0051] As the non-reactive dispersion medium, a ketone-based solvent such as methyl ethyl ketone (MEK) or methyl isobutyl ketone (MIBK), an alcohol-based solvent such as methanol (MeOH) or propylene glycol monomethyl ether (PGME), or an ester-based solvent such as propylene glycol monomethyl ether acetate (PGMEA) may be used. In the case of a non-reactive dispersion medium, a resin composition may be prepared by mixing a base resin and inorganic oxide particles dispersed in the dispersion medium, and then removing a part of the dispersion medium.
[0052] From the viewpoint of excellent dispersibility in the resin composition, the average primary particle size of the inorganic oxide particles may be 650 nm or less, preferably 600 nm or less, more preferably 500 nm or less, and even more preferably 400 nm or less. From the viewpoint of excellent strength after curing, the average primary particle size of the inorganic oxide particles is preferably 5 nm or more, more preferably 10 nm or more. The average primary particle size can be measured, for example, by image analysis of an electron microscope photograph, a light scattering method, a BET method, etc. The dispersion medium in which the primary particles of the inorganic oxide particles are dispersed appears transparent to the naked eye when the particle size of the primary particles is small. When the particle size of the primary particles is relatively large (40 nm or more), the dispersion medium in which the primary particles are dispersed appears cloudy, but no sediment is observed.
[0053] The content of the inorganic oxide particles may be 1% by mass or more and 45% by mass or less, 2% by mass or more and 40% by mass or less, or 3% by mass or more and 35% by mass or less, based on the total amount of the resin composition. When the content of the inorganic oxide particles is 1% by mass or more, a tough cured product is easily formed. When the content of the inorganic oxide particles is 45% by mass or less, a cured product in which the inorganic oxide particles are suitably dispersed is easily formed. The total amount of the resin composition and the total amount of the cured product of the resin composition can be substantially the same.
[0054] Examples of the lubricant include silicone-based lubricants such as silicone oil. The silicone oil may be a high molecular weight silicone oil or a modified silicone oil in which a part of a dimethylsiloxane skeleton is modified to an organic group. Examples of the modified silicone oil include polyether-modified, amine-modified, epoxy-modified, mercapto-modified, (meth)acrylic-modified, or carboxyl-modified silicone oil. The colored secondary resin layer has a lower curability than a secondary resin layer that does not contain a pigment, and the adhesion to the tape resin layer is easily increased, but by using a resin composition containing a silicone-based lubricant, it is easy to adjust the adhesion between the colored secondary resin layer and the ribbon resin.
[0055] The content of the silicone-based lubricant in the colored secondary resin layer is preferably 2% by mass or less, more preferably 0.1% by mass or more and 1% by mass or less, based on the total amount of the resin composition for the secondary resin layer. If the molecular weight of the silicone-based lubricant is too small, it is likely to precipitate, and the adhesion to the connecting resin layer or the primary resin layer is reduced. If the molecular weight of the silicone-based lubricant is too large, the compatibility with the resin component is reduced. The average molecular weight of the silicone oil is preferably 10,000 or more and 100,000 or less.
[0056] The photoacid generator is A + B - Examples of the photoacid generator include sulfonium salts such as UVACURE1590 (manufactured by Daicel-Cytec), CPI-100P, 110P, and 210S (manufactured by San-Apro), and iodonium salts such as Omnicat 250 (manufactured by IGM Resins), WPI-113 (manufactured by Fujifilm Wako Pure Chemical Industries), and Rp-2074 (manufactured by Rhodia Japan).
[0057] The Young's modulus of the colored secondary resin layer is preferably 1200 MPa or more, more preferably 1300 MPa or more, and even more preferably 1400 MPa or more at 23° C. The Young's modulus of the colored secondary resin layer may be 3000 MPa or less, 2500 MPa or less, 2000 MPa or less, or 1800 MPa or less at 23° C. When the Young's modulus of the colored secondary resin layer is 1200 MPa or more, the lateral pressure resistance is easily improved, and when it is 3000 MPa or less, the layer has an appropriate breaking elongation, so that the layer is less likely to break when the coating is removed, and has excellent coating removability.
[0058] The primary resin layer 14 can be formed by curing an ultraviolet-curable resin composition containing a photopolymerizable compound, a photopolymerization initiator, and a silane coupling agent. The polymerizable compound, the photopolymerization initiator, and the silane coupling agent can be appropriately selected from those exemplified as the resin composition forming the colored secondary resin layer. However, the resin composition forming the primary resin layer has a different composition from the resin composition forming the colored secondary resin layer.
[0059] In order to prevent the occurrence of voids in the optical fiber, the Young's modulus of the primary resin layer is preferably 0.04 MPa or more and 0.8 MPa or less at 23°C, more preferably 0.05 MPa or more and 0.7 MPa or less, and even more preferably 0.05 MPa or more and 0.6 MPa or less.
[0060] The characteristics of the optical fiber applicable to the present disclosure may be, for example, a mode field diameter at a wavelength of 1310 nm of 8.2 μm or more and 9.6 μm or less, a cable cutoff wavelength of 1260 nm or less, and a loss increase at a wavelength of 1625 nm when wound 100 times (per 100 turns) around a mandrel of a radius of 30 mm of 0.1 dB or less, and a loss increase at a wavelength of 1625 nm when wound 10 times (per 10 turns) around a mandrel of a radius of 15 mm of 15 mm of 10 turns.
[0061] Fig. 2 is a schematic cross-sectional view showing an optical fiber ribbon according to one embodiment. The optical fiber ribbon 100 has a plurality of optical fibers 10 and a connecting resin layer 40 in which the optical fibers 10 are (integrally) coated with a ribbon resin and connected. In Fig. 2, four optical fibers 10 are shown as an example, but the number is not particularly limited.
[0062] The optical fibers 10 may be integrated in a state where they are in contact with each other and arranged in parallel, or some or all of the optical fibers 10 may be integrated in a state where they are arranged in parallel with a fixed interval. However, when some or all of the optical fibers 10 are integrated in a state where they are arranged in parallel with a fixed interval, the average center-to-center distance F between adjacent optical fibers 10 is 220 μm or more and 280 μm or less. m The center distance may be 220 μm or more and 280 μm or less. m In the case of the following, it is easy to place the optical fibers in the existing V-groove, and it is possible to obtain an optical fiber ribbon with excellent bulk fusion properties. The thickness T of the optical fiber ribbon 100 depends on the outer diameter of the optical fibers 10, but may be 164 μm or more and 285 μm or less.
[0063] The resin composition for the ribbon may contain a urethane (meth)acrylate, a monomer, and a photopolymerization initiator. The urethane (meth)acrylate, the monomer, and the photopolymerization initiator may be appropriately selected from those exemplified in the resin composition for forming the colored secondary resin layer. The ribbon resin (connecting resin) contains a cured product of the urethane (meth)acrylate, thereby improving the elasticity of the connecting resin layer.
[0064] The ribbon resin may further contain a silicone-based lubricant. When the ribbon resin contains a silicone-based lubricant, it is possible to suppress the optical fiber ribbons from sticking to each other, and it becomes easier to reduce an increase in loss when the optical fiber ribbons are made into a cable.
[0065] The Young's modulus of the ribbon resin may be 50 MPa or more and 900 MPa or less, or 100 MPa or more and 800 MPa or less, at 23° C., from the viewpoint of providing both lateral pressure resistance and flexibility to the optical fiber ribbon.
[0066] Fig. 3 is a schematic cross-sectional view showing an example of an optical fiber ribbon in which optical fibers are integrated in a state in which they are arranged in parallel at regular intervals. The optical fiber ribbon 100A shown in Fig. 3 is formed by connecting six pairs of two optical fibers 10 at regular intervals with a ribbon resin. The ribbon resin forms a connecting resin layer 40.
[0067] When the optical fibers 10 are arranged in parallel at regular intervals, i.e., when adjacent optical fibers 10 are joined via ribbon resin without touching each other, the thickness of the connection part at the center of the optical fibers 10 may be 150 μm or more and 220 μm or less. Since the optical fiber ribbon is easily deformed when being stored in a cable, the optical fiber ribbon may have a recess at the connection part of the optical fibers. The recess may be formed in a triangular shape with a narrowing angle on one side of the connection part.
[0068] The optical fiber ribbon according to the present embodiment may have connecting portions and non-connecting portions intermittently in the longitudinal and width directions. FIG. 4 is a plan view showing the appearance of the optical fiber ribbon according to one embodiment. The optical fiber ribbon 100B has a plurality of optical fibers, a plurality of connecting portions 20, and a non-connecting portion (severed portion) 21. The non-connecting portions 21 are formed intermittently in the longitudinal direction of the optical fiber ribbon. The optical fiber ribbon 100B is an intermittently connected type optical fiber ribbon in which the connecting portions 20 and the non-connecting portions 21 are intermittently provided in the longitudinal direction for every two optical fibers 10A. The "connecting portion" refers to a portion where adjacent optical fibers are integrated via a connecting resin layer, and the "non-connecting portion" refers to a portion where adjacent optical fibers are not integrated via a connecting resin layer and there is a gap between the optical fibers.
[0069] In the optical fiber ribbon having the above configuration, the non-connecting portions 21 are intermittently provided at the connecting portions 20 provided for every two cores, so that the optical fiber ribbon is easily deformed. Therefore, when mounting the optical fiber ribbon on an optical fiber cable, the optical fiber ribbon can be easily rolled up and mounted, so that the optical fiber ribbon is suitable for high-density mounting. In addition, the connecting portions 20 can be easily torn starting from the non-connecting portions 21, so that the optical fibers 10 in the optical fiber ribbon can be easily separated into individual cores.
[0070] An intermittently connected type optical fiber ribbon can be manufactured using a manufacturing device with a swing blade, as described in, for example, Japanese Patent Nos. 5779940, 5880270, and 5737220.
[0071] <Optical fiber cable> The optical fiber cable according to the present embodiment has the above-mentioned optical fiber ribbon mounted therein. An example of the optical fiber cable is a slot-type optical fiber cable having a plurality of slot grooves. The optical fiber ribbon can be mounted in the slot grooves so that the mounting density in each slot groove is about 25% to 65%. The mounting density means the ratio of the cross-sectional area of the optical fiber ribbon mounted in the slot groove to the cross-sectional area of the slot groove. EXAMPLES
[0072] The present disclosure will be described in more detail below by showing the results of evaluation tests using examples and comparative examples according to the present disclosure. Note that the present disclosure is not limited to these examples.
[0073] [Resin composition for secondary resin layer] (Photopolymerizable compound) As photopolymerizable compounds, polypropylene glycol having a molecular weight of 800, urethane acrylate which is a reaction product of isophorone diisocyanate and 2-hydroxyethyl acrylate, epoxy acrylate having a bisphenol A skeleton, isobornyl acrylate, N-vinyl caprolactam, and tripropylene glycol diacrylate were prepared.
[0074] (Photopolymerization initiator) As photopolymerization initiators, 2,4,6-trimethylbenzoyldiphenylphosphine oxide (TPO) and 1-hydroxycyclohexyl phenyl ketone (Omnirad 184) were prepared.
[0075] (Silicone lubricant) As a silicone-based lubricant, modified silicone oil (polyether modified, average molecular weight 15,000) was prepared.
[0076] (Pigments) Titanium oxide and copper phthalocyanine were prepared as pigments.
[0077] (Preparation Example 1) Resin composition S1 for the colored secondary resin layer was prepared by mixing 40 parts by weight of urethane acrylate, 25 parts by weight of epoxy acrylate, 6.2 parts by weight of isobornyl acrylate, 5 parts by weight of N-vinyl caprolactam, 15 parts by weight of tripropylene glycol diacrylate, 0.8 parts by weight of TPO, 1.0 part by weight of Omnirad184, 1.0 part by weight of silicone oil, 3.0 parts by weight of titanium oxide, and 3.0 parts by weight of copper phthalocyanine.
[0078] (Preparation Example 2) Resin composition S2 was prepared in the same manner as in Preparation Example 1, except that the amount of isobornyl acrylate was changed to 5.5 parts by mass and the amount of TPO was changed to 1.5 parts by mass.
[0079] (Preparation Example 3) Resin composition S3 was prepared in the same manner as in Preparation Example 1, except that the amount of isobornyl acrylate was changed to 5.0 parts by mass and the amount of TPO was changed to 2.0 parts by mass.
[0080] (Preparation Example 4) Resin composition S4 was prepared in the same manner as in Preparation Example 1, except that the amount of urethane acrylate was changed to 25 parts by mass, the amount of epoxy acrylate was changed to 40 parts by mass, the amount of isobornyl acrylate was changed to 5.0 parts by mass, and the amount of TPO was changed to 2.0 parts by mass.
[0081] (Preparation Example 5) Resin composition S5 was prepared in the same manner as in Preparation Example 1, except that the amount of urethane acrylate was changed to 15 parts by mass, the amount of epoxy acrylate was changed to 50 parts by mass, the amount of isobornyl acrylate was changed to 5.0 parts by mass, and the amount of TPO was changed to 2.0 parts by mass.
[0082] (Preparation Example 6) Resin composition S6 was prepared in the same manner as in Preparation Example 1, except that the amount of urethane acrylate was changed to 7.5 parts by mass, the amount of epoxy acrylate was changed to 60 parts by mass, the amount of isobornyl acrylate was changed to 2.5 parts by mass, and the amount of TPO was changed to 2.0 parts by mass.
[0083] (Preparation Example 7) Resin composition S7 was prepared in the same manner as in Preparation Example 1, except that the amount of urethane acrylate was changed to 7.5 parts by mass, the amount of epoxy acrylate was changed to 60 parts by mass, the amount of isobornyl acrylate was changed to 2.0 parts by mass, and the amount of TPO was changed to 2.5 parts by mass.
[0084] (Preparation Example 8) Resin composition S8 was prepared in the same manner as in Preparation Example 1, except that the amount of urethane acrylate was changed to 7.5 parts by mass, the amount of epoxy acrylate was changed to 60 parts by mass, the amount of isobornyl acrylate was changed to 1.5 parts by mass, and the amount of TPO was changed to 3.0 parts by mass.
[0085] (Preparation Example 9) Resin composition S9 was prepared in the same manner as in Preparation Example 1, except that the amount of isobornyl acrylate was changed to 6.8 parts by mass and the amount of TPO was changed to 0.25 parts by mass.
[0086] (Preparation Example 10) Resin composition S10 was prepared in the same manner as in Preparation Example 1, except that the amount of urethane acrylate was changed to 7.0 parts by mass, the amount of epoxy acrylate was changed to 60 parts by mass, the amount of isobornyl acrylate was changed to 1.0 part by mass, and the amount of TPO was changed to 4.0 parts by mass.
[0087] [Resin composition for primary resin layer] A resin composition for the primary resin layer was prepared by mixing 75 parts by mass of urethane acrylate, which is a reaction product of polypropylene glycol with a molecular weight of 2000, 2,4-tolylene diisocyanate, 2-hydroxyethyl acrylate and methanol, 12 parts by mass of nonylphenol EO-modified acrylate, 6 parts by mass of N-vinyl caprolactam, 2 parts by mass of 1,6-hexanediol diacrylate, 1 part by mass of TPO, and 1 part by mass of γ-mercaptopropyltrimethoxysilane.
[0088] [Resin composition for ribbons] Polypropylene glycol with a molecular weight of 1000, 2,4-tolylene diisocyanate and 2-hydroxyethyl acrylate Urethane acrylate, which is the reaction product of A resin composition for ribbons was prepared by mixing 70 parts by mass of the above, 10 parts by mass of 2-phenoxyethyl acrylate, 13 parts by mass of tripropylene glycol diacrylate, 5 parts by mass of N-vinyl caprolactam, 1 part by mass of TPO, and 1 part by mass of Omnirad 184.
[0089] [Fabrication of optical fiber] A resin composition for the primary resin layer and a resin composition for the secondary resin layer were applied to the outer circumference of a glass fiber having a diameter of 125 μm, which is composed of a core and a clad, and then the resin composition was cured by irradiating with ultraviolet light to form a primary resin layer having a thickness of 20 μm and a colored secondary resin layer having a thickness of 17.5 μm on the outer circumference of the primary resin layer, thereby producing an optical fiber having an outer diameter of 200 μm. The drawing speed was 1500 m / min.
[0090] [Fabrication of optical fiber ribbons] The 12 colored optical fibers were coated with a resin composition for ribbons, and then the resin composition was irradiated with ultraviolet light to harden the composition and form a connecting resin layer, thereby producing the optical fiber ribbon shown in Fig. 5. Fig. 5 is a schematic cross-sectional view showing the produced optical fiber ribbon 100C. The optical fibers 10 are connected at regular intervals by the resin for ribbons. The thickness of the connection between the optical fibers was 180 μm to 220 μm, the center-to-center distance between adjacent optical fibers was 255 μm, the thickness of the optical fiber ribbon was 230 μm ± 15 μm, and the width of the optical fiber ribbon was 3.05 mm ± 0.05 mm.
[0091] [evaluation] The optical fibers and optical fiber ribbons were evaluated as follows. Table 1 shows the evaluation results of the optical fibers and optical fiber ribbons produced in the examples, and Table 2 shows the evaluation results of the optical fibers and optical fiber ribbons produced in the comparative examples.
[0092] (Young's Modulus) The Young's modulus of the primary resin layer was measured by the Pullout Modulus (POM) method at 23°C. Two points of the optical fiber were fixed with two chuck devices, and the coating resin layer (primary resin layer and secondary resin layer) between the two chuck devices was removed. Then, one chuck device was fixed, and the other chuck device was gently moved in the opposite direction to the fixed chuck device. When the length of the part of the optical fiber sandwiched between the moving chuck devices is L, the amount of movement of the chuck is Z, the outer diameter of the primary resin layer is Dp, the outer diameter of the glass fiber is Df, the Poisson's ratio of the primary resin layer is n, and the load during the movement of the chuck device is W, the Young's modulus of the primary resin layer was calculated from the following formula. The Young's modulus of the primary resin layer was 0.6 MPa. Young's modulus (MPa) = ((1 + n)W / πLZ) × ln(Dp / Df)
[0093] The Young's modulus of the colored secondary resin layer was determined by conducting a tensile test (gauge length: 25 mm) at 23°C using a pipe-shaped coating resin layer (length: 50 mm or more) obtained by immersing an optical fiber in a solvent (ethanol:acetone = 3:7) and removing the glass fiber, and then obtaining the 2.5% secant value.
[0094] (Amount of P-Sn complex) The surface of the colored secondary resin layer was analyzed by TOF-SIMS. The equipment used was a TRIFT V nanoTOF, with the ion species Au+ and an acceleration voltage of 30 kV. Measurements were performed by irradiating an ion beam from the side of the optical fiber. The ratio of the peak value at +337 (m / z) (representing the amount of phosphorus-tin complex) to the peak value at +59 (m / z) (representing the amount of hydrocarbon) (peak value at +337 / peak value at +59) was expressed in ppm and used as the amount of P-Sn complex.
[0095] (single core separation) A 1m optical fiber ribbon was stored for 60 days in an environment of 85℃ and 85%. A few centimeters from the end of the optical fiber ribbon was exposed to a single core, and separated in the longitudinal direction of the optical fiber ribbon. Although the ribbon resin was likely to remain at the end of the optical fiber ribbon, if 1m could be peeled off without the ribbon resin breaking, it was rated as "A". If 1m could be peeled off within 5 cuts of the ribbon resin, it was rated as "B". If the ribbon resin was cut 6 or more times, if the ribbon resin could not be peeled off, or if it could be peeled off but peeling occurred in the colored layer, it was rated as "C".
[0096] (peeling resistance) After compressing the optical fiber ribbon widthwise 10 times, if there was no core spill, it was rated as "OK", and if there was core spill, it was rated as "NG".
[0097] (Cable loss characteristics) The optical fiber cable was left in a 23°C environment, and the transmission loss was measured when the signal light had a wavelength of 1.55 μm. The measured values were evaluated according to the following criteria. A: Transmission loss is 0.25dB / km or less. B: Transmission loss is greater than 0.25 dB / km and less than 0.3 dB / km. C: Transmission loss is more than 0.3 dB / km.
[0098] [Table 1]
[0099] [Table 2] [Explanation of symbols]
[0100] 10,10A Optical Fiber 11 cores 12 Clad 13 Glass Fiber 14 Primary resin layer 15 Colored secondary resin layer 16 Resin coating layer 20 Connecting part 21 Unconnected part 40 Connecting resin layer 100, 100A, 100B, 100C Optical Fiber Ribbon
Claims
1. An optical fiber ribbon having a plurality of optical fibers arranged in parallel and a connecting resin layer including a ribbon resin that coats and connects the plurality of optical fibers, The outer diameter of each of the plurality of optical fibers is 220 μm or less, Each of the plurality of optical fibers includes a glass fiber including a core and a cladding, a primary resin layer that is in contact with the glass fiber and covers the glass fiber, and a colored secondary resin layer that covers the primary resin layer, the colored secondary resin layer comprises a cured product of a resin composition containing 2,4,6-trimethylbenzoyldiphenylphosphine oxide as a photopolymerization initiator, a polyfunctional monomer having a bisphenol skeleton, and a silicone-based lubricant; the content of phosphorus contained in the colored secondary resin layer is 0.03% by mass or more and 0.30% by mass or less, and the amount of phosphorus-tin complex on the surface of the colored secondary resin layer is 300 ppm or more and 7000 ppm or less, The optical fiber ribbon, wherein the ribbon resin comprises a cured product of urethane (meth)acrylate.
2. 2. The optical fiber ribbon according to claim 1, wherein the amount of the phosphorus-tin complex is 500 ppm or more and 6000 ppm or less.
3. 3. The optical fiber ribbon according to claim 1, wherein an average distance between the centers of adjacent optical fibers among said plurality of optical fibers is 220 μm or more and 280 μm or less.
4. The optical fiber ribbon according to any one of claims 1 to 3, wherein the resin composition further contains 1-hydroxycyclohexyl phenyl ketone as a photopolymerization initiator.
5. 5. The optical fiber ribbon according to claim 1, wherein the colored secondary resin layer has a Young's modulus of 1200 MPa or more at 23°C.
6. 6. The optical fiber ribbon according to claim 1, wherein the optical fiber ribbon has intermittent connected portions and non-connected portions in the longitudinal and width directions.
7. 7. The optical fiber ribbon according to claim 1, wherein the connecting resin layer has a recess in a portion that connects adjacent optical fibers among the plurality of optical fibers.
8. An optical fiber cable comprising an optical fiber ribbon according to any one of claims 1 to 7 mounted therein.
Citation Information
Patent Citations
Coated optical fiber core and coated optical fiber unit
JP1994242355A
Radiation-curable ink composition
JP2001524223A
Optical fiber ribbon and optical fiber cable storing the same
JP2013088617A
Production method of optical fiber
JP2018177630A
Optical fiber
JP2019045517A